2006
DOI: 10.1007/s00122-006-0339-6
|View full text |Cite
|
Sign up to set email alerts
|

A branched-chain amino acid aminotransferase gene isolated from Hordeum vulgare is differentially regulated by drought stress

Abstract: Differential display was used to isolate cDNA clones showing differential expression in response to ABA, drought and cold in barley seedling shoots. One drought-regulated cDNA clone (DD12) was further analyzed and found to encode a branched-chain amino acid aminotransferase (HvBCAT-1). A genomic clone was isolated by probing the Morex BAC library with the cDNA clone DD12 and the structure of Hvbcat-1 was elucidated. The coding region is interrupted by six introns and contains a predicted mitochondrial transit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…Increased accumulation of tryptophan in wheat under drought is also supported by previous studies [21] [50], and Arabidopsis [51], and similar result was found in this study. Taylor et al (2004) reported that branched chain amino acids are a source of alternate energy when Arabidopsis plants were under sugar starvation, which is a common phenomenon under stress [52].…”
Section: Discussionsupporting
confidence: 92%
“…Increased accumulation of tryptophan in wheat under drought is also supported by previous studies [21] [50], and Arabidopsis [51], and similar result was found in this study. Taylor et al (2004) reported that branched chain amino acids are a source of alternate energy when Arabidopsis plants were under sugar starvation, which is a common phenomenon under stress [52].…”
Section: Discussionsupporting
confidence: 92%
“…The enzymes are also involved in the degradation of BCAA to provide an alternative carbon source under stress conditions in plants, animal and bacteria. Barley BCATs and Arabidopsis BCAT2 are induced by drought stress and sucrose starvation, respectively [19,20]. The observation that sucrose starvation enhanced the expression of VuBCAT2 prompted us to propose a hypothesis that an increased degradation of BCAA by BCAT results in inactivation of cowpea TOR, in tern, leading to induction of autophagy via ATG1-ATG13 cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, low energy stresses such as reduced photosynthesis and/or sucrose starvation appeared to induce daramatic change of amino acid catabolism for asparagine biosynthesis by inducing the expression of asparagine synthase (AtASN1), proline dehydrogenase1 (AtProDH), and branched chain aminoacid transaminase (AtBCAT2) [18,19]. Among cowpea homlog genes amino acid catabolic-related enzymes, VuASN1 (TC7410), VuProDH (TC15194) and VuBCAT2 (TC3413) were identified to have the highest similarites of 82%, 62% and 62% in deduced amino acid sequences to AtASN1 (At3g47340), AtProDH (At3g30775) and AtBCAT2 (At1g10070), respectively.…”
Section: Induction Of Amino Acid Catabolism-related Genes and A Bzip mentioning
confidence: 99%
“…Surprisingly, it was found that AtBCAT-4 participates in the chain elongation pathway of Met-derived glucosinolate biosynthesis, which has a close evolutionary relationship to the Leu biosynthesis pathway (Schuster et al 2006). A newly identiWed BCAT gene from barley, HvBCAT-1, is inducible by drought stress (Malatrasi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is a small family of BCAT genes in plants, which have been characterized in some species such as Solanum tuberosum (potato), Arabidopsis and Hordeum vulgare (barley) (Campbell et al 2001;Diebold et al 2002;Malatrasi et al 2006). Two BCAT genes (StBCAT-1, StBCAT-2) isolated from S. tuberosum are diVerentially expressed.…”
Section: Introductionmentioning
confidence: 99%